Pengaruh Kualitas Produk dan Harga terhadap Minat Beli Gelato Berbahan Dasar Susu Kedelai pada GlacéCo - Sitepu, Rasidin Karo Karo; Marsellina, Elisa; Imtiyaaz Anggraeni; Rachel Azahra; Risma Dianitami; Mardagus, Wulandari (Jurnal Agrosains dan Teknologi, 2025)
GlacéCo is a company engaged in gelato production that strives to maintain product quality while setting competitive prices in accordance with consumer preferences and market conditions. This study aims to examine the influence of product quality and price on consumers’ purchase intention toward GlacéCo gelato. The method used is Structural Equation Modeling-Partial Least Squares (SEM-PLS), with primary data collected through questionnaires and interviews. The research sample consisted of 50 respondents selected using purposive sampling, a type of non-probability sampling. The results show that product quality and price have a positive and significant effect on consumers’ purchase intention. These findings emphasize the importance for GlacéCo to continuously improve product quality and set appropriate prices in order to increase consumer interest in purchasing. Keywords: Gelato, Price, Product Quality, Purchase Intention